2018
DOI: 10.1037/rev0000103
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of polychronization and feature binding in a spiking neural network model of the primate ventral visual system.

Abstract: We present a hierarchical neural network model, in which subpopulations of neurons develop fixed and regularly repeating temporal chains of spikes (polychronization), which respond specifically to randomized Poisson spike trains representing the input training images. The performance is improved by including top-down and lateral synaptic connections, as well as introducing multiple synaptic contacts between each pair of pre- and postsynaptic neurons, with different synaptic contacts having different axonal del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(88 citation statements)
references
References 53 publications
(101 reference statements)
1
87
0
Order By: Relevance
“…However, real neurons in the brain communicate with each other using discrete electrical pulses called action potentials or 'spikes'. In future work, we plan to run simulations of the head direction system using a spiking neural network model that can more accurately mimic the temporal dynamics of neurons and synapses (Eguchi et al 2018;Isbister et al 2018). In particular, this will enable us to implement realistic neuronal and synaptic time constants governing, for example, the exponential decays of both cell voltages and synaptic conductances.…”
Section: Discussionmentioning
confidence: 99%
“…However, real neurons in the brain communicate with each other using discrete electrical pulses called action potentials or 'spikes'. In future work, we plan to run simulations of the head direction system using a spiking neural network model that can more accurately mimic the temporal dynamics of neurons and synapses (Eguchi et al 2018;Isbister et al 2018). In particular, this will enable us to implement realistic neuronal and synaptic time constants governing, for example, the exponential decays of both cell voltages and synaptic conductances.…”
Section: Discussionmentioning
confidence: 99%
“…A simulator whose performance is unaffected by axonal delays is particularly desirable given the range of research avenues which leverage delays within spiking neural networks. SNN models investigating a range of subjects including sound localization, reservoir computing, auditory processing and visual feature binding (Goodman and Brette, 2010;Paugam-Moisy et al, 2008;Erfanian Saeedi et al, 2016;Eguchi et al, 2018) are but a few of the many studies which implement multiple axonal delay values within a single study for modelling purposes. Spike is a simulator designed to optimise this process.…”
Section: Delay Insensitivementioning
confidence: 99%
“…How might the visual cortex represent such a hierarchy of visual features, as well as the hierarchical binding relations between these features, at every spatial scale and across the entire visual field? Eguchi et al [ 9 ] have recently shown how this may be achieved within a biologically realistic hierarchical neural network model of the primate ventral visual system with the following properties. (1) The model is a ‘spiking’ neural network, in which the timings of the spikes emitted by neurons are explicitly represented.…”
Section: Introductionmentioning
confidence: 99%
“… (5) The network may incorporate multiple synaptic connections between each pair of pre- and postsynaptic neurons, where these connections have different axonal transmission delays. Eguchi et al [ 9 ] showed that this allows the STDP to selectively strengthen specific synaptic connections with particular axonal transmission delays. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation